2015
DOI: 10.1155/2015/760313
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Vitamin D Receptor Genetic Variants on Bone Mineral Density and Osteoporosis in Chinese Postmenopausal Women

Abstract: Growing evidence indicates that the vitamin D receptor (VDR) gene is an important candidate gene for influencing the development of osteoporosis. The aim of the study was to evaluate the potential association between genetic variants of VDR gene and bone mineral density (BMD) and osteoporosis in Chinese postmenopausal women. The study included 970 Chinese postmenopausal women at the postmenopausal osteoporosis (482) and healthy controls (488). The BMD of lumbar spine (L2–4 anterior-posterior view), femoral nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Under this condition, oxygen and blood supply to myocardial cells is reduced, leading to necrosis or even death (9). Advances in clinical research have shown that Hcy, NO and other substances can reflect impaired coronary vascular endothelial function (10). Hcy is an intermediate product of the metabolism of methionine and cysteine and cannot be synthesized in human body.…”
Section: Discussionmentioning
confidence: 99%
“…Under this condition, oxygen and blood supply to myocardial cells is reduced, leading to necrosis or even death (9). Advances in clinical research have shown that Hcy, NO and other substances can reflect impaired coronary vascular endothelial function (10). Hcy is an intermediate product of the metabolism of methionine and cysteine and cannot be synthesized in human body.…”
Section: Discussionmentioning
confidence: 99%
“…VDR modulation influences the expression and transcription of genes involved in bone mass formation and calcium uptake, such as osteocalcin and calcium‐binding proteins . The VDR gene is a polygenetic gene, and single nucleotide polymorphisms (SNPs) of VDR gene could influence the expression and function of VDR protein, which is proven to influence the risk of osteoporosis …”
Section: Introductionmentioning
confidence: 99%
“…first investigated that VDR genetic variants could predict osteocalcin levels in Caucasian women. Subsequently, a number of studies were conducted to investigate the association between VDR genetic variants (e.g., BsmI [rs1544410], ApaI [rs7975232], Tru9I [rs757343]) and osteoporosis in different ethnic groups, but these studies reported conflicting results . These different results might have been caused by racial and regional differences in the studied patients, as well as by the limitation of the number of patients per study.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, cost-effective intervention policies must urgently be identified in an attempt to minimize the impact of fractures (2). Osteoporosis has been associated with various risk factors, particularly female gender (3), advanced age (4), dietary calcium (5), vitamin D status (6), obesity (7), chronic obstructive pulmonary disease (COPD) (8), stress (9), gastric bypass surgery (10,11), genetic variants (12)(13)(14), alcoholism (15) and smoking habit (16).…”
mentioning
confidence: 99%
“…Some studies which were conducted on Caucasian and Asian women suggest that polymorphisms in the vitamin D receptor (VDR) gene are associated with BMD in postmenopausal women (21). VDR modulation influences the expression and transcription of genes which are involved in bone mass formation and calcium uptake, such as osteocalcin and calcium-binding proteins (22). Polymorphism of the VDR gene alleles may account for the major part of the heritable component of bone density in women, possibly mediated in part by impaired calcium absorption from the bowel (1).…”
mentioning
confidence: 99%